A study of the use of metadata standards for cataloguing Internet resources. - Low, Ke Khoon. (2008)
The study explored and investigated the various ways in which Dublin Core, developed by the Dublin Core Metadata Initiative (DCMI) through a series of workshops since 1995, has been used to describe and organize information on the Internet.